What do the narratives tell us? Exploring the implementation of the Athena SWAN Ireland Charter - O'Mullane, Monica (Frontiers in Sociology, 2023)
Due to the systemic inequalities enduring in career progression pathways in the Irish higher education sector, the Athena SWAN Ireland Charter (ASIC), a gender equality accreditation programme, is being implemented. Using a theoretical approach blending insights from feminist institutionalism with literature on the role of narratives in policy implementation, this article reveals the complex nature of subjective engagement with policy implementation processes. The article discusses an empirical study of Athena SWAN Ireland Charter implementation across three purposively chosen Irish universities, interviewing 26 key institutional actors tasked with implementing the ASIC locally. Narrative themes emerging as dominant from the data include a lack of operational knowledge, desire for a nationally contextualised programme, ambiguity, championing, ‘happy talk’ and identifying points of resistance. Literature on the role of narrative accounts highlighting a diversity of perceptions in policy and programme implementation is strengthened by this study’s findings. A feminist institutionalist lens highlights the gendered nature of the operationalisation of the Charter work and the vague and detached ‘happy talk’ engaged predominantly by senior men leaders. Findings from this empirical study highlight the importance of exploring the narrative accounts of key actors in order to gain a holistic understanding of the nuanced implementation process, beyond the normative assumptions inherent in the Charter implementation.